Accountability Bonds – Reconciling Fiscal Policy Based on Market Discipline with Financial Stability - Clemens Fuest; Friedrich Heinemann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Reforming the Eurozone is a top priority on the European policy agenda. France and Germany are expected to launch a joint initiative to reform the institutions of the currency union. To be successful, this initiative will have to be acceptable not only to Germany and France, but to all member states including those plagued by high debt levels and sluggish economic growth. The issue of market discipline in national fiscal policy and sovereign debt restructuring dominates the debate over Eurozone reform. While the German government emphasizes the role of market discipline and the no-bailout-rule, the French government is more skeptical, arguing that sovereign debt restructuring may give rise to financial instability. Public debt levels are high (over 130 percent of GDP in Italy, for example), banks are holding large quantities of government debt, and their ability to absorb losses from a debt restructuring is limited. In this situation, reforms that make debt restructuring more likely could undermine investor confidence and trigger a financial crisis. There is nevertheless a growing awareness that fiscal governance in the Eurozone will not work without credible forms of public debt restructuring. Such restructuring can only be avoided with far reaching mutualization of government debt. This, however, would be incompatible with preserving national sovereignty in fiscal policy. European control over national fiscal policies is weak and will remain so for the fore-seeable future. At the same time, the no-bailout-rule and plans for public debt restructuring can only remain credible if their implementation does not lead to a financial crisis. Highly-indebted countries are unlikely to support fiscal policy reforms dominated by market discipline either, especially if they massively raise debt servicing costs or make it harder to roll over existing debt. Two years ago,~EconPol network economists Clemens Fuest (ifo Institute) and Friedrich Heinemann (ZEW) published a proposal for a new form of government bonds called Accountability Bonds aimed at reviving market discipline into the Eurozone without endangering fiscal and financial stability. This paper revisits their concept of accountability bonds in the light of current developments and responds to criticism of it.
Keywords: 330